Immediate economic history of Iraq - Dinç, Ahmet (Management, 2012)
I have analyzed effects of the economic crisis, which began in the USA, on Northern Iraq under three main titles: First, I studied the economic history of Iraq. Second, I analyzed the effects of it in Northern Iraq. Finally, I interviewed entrepreneurs about the effects of crisis on private sectors in this region. I have been in northern Iraq for three years. I have tried to reach original sources, have interviewed people in the government and examinedthe impact of the crisis on the people and government. It was seen that the country's economy, is mostly based on the oil sectors, so we especially highlighted oil production and revenue, which have been affected indirectly from the global crisis.
Keywords: ekonomska kriza; ekonomska zgodovina; Irak; Iraq; naftna industrija